2022
DOI: 10.1111/zph.12929
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a decrease in sales of antimicrobials of very high importance for humans in dairy herds after a new regulation restricting their use in Quebec, Canada

Abstract: In the province of Quebec, Canada, a new regulation restricting usage of antimicrobials of very high importance for human health (Health Canada: category 1 antimicrobials) in production animals is effective since February 2019. The objective of this study was to estimate changes in AM sales in dairy herds after the implementation of the regulation. Therefore, invoice data were extracted from veterinary software, Vet-Expert, used by most dairy veterinarians in the province of Quebec, and antimicrobial quantitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This change presented a layer of friction and oversight in antimicrobial acquisition, as it became less convenient for farms to procure antimicrobials and necessitated veterinary approval. Further regulations came into effect in Québec in 2019, directed at reducing the use of Category I. Millar et al (18) found that these regulations were extremely effective and may provide a further intervention to address ceftiofur usage (18). Another change was the introduction of new drugs and the removal of others from 2007 until 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change presented a layer of friction and oversight in antimicrobial acquisition, as it became less convenient for farms to procure antimicrobials and necessitated veterinary approval. Further regulations came into effect in Québec in 2019, directed at reducing the use of Category I. Millar et al (18) found that these regulations were extremely effective and may provide a further intervention to address ceftiofur usage (18). Another change was the introduction of new drugs and the removal of others from 2007 until 2020.…”
Section: Discussionmentioning
confidence: 99%
“…There was a shift from polymyxin use to third-generation cephalosporins among Category I antimicrobials, likely attributable to the of IMM ceftiofur in 2008 and the withdrawal of polymyxin-containing products from the Canadian market in 2020. New regulations regarding Category I antimicrobials came into effect in Québec in 2019, which Millar et al (18) showed caused a profound reduction in the use of these products. However, this occurred after this study's second assessment of AMU in Québec.…”
Section: Comparison Of Amu Between 2007-2008 and 2019-2020mentioning
confidence: 99%
“…This new policy prohibits the use of these antimicrobials for disease prevention in food-producing animals and indicates that veterinarians must prove that an antimicrobial of lesser importance for humans would not be effective (via antimicrobial susceptibility testing) or available before prescribing them. An important decrease in Category 1 AMU in dairy farms was observed following the implementation of this policy [59]. In addition, other factors such as the uncertainty surrounding the impact of the current COVID-19 pandemic on AMU in animal production [20], the global geopolitical changes aimed at promoting the resilience of food production systems in each country, the change in consumption habits and in the global demand for animal protein, regulatory changes (e.g., requiring fees paid by veterinary drug users) [49], the creation of national reduction targets, and the changes in data-collection systems (as well as the possibility of developing new effective alternatives to antibiotics in farm animals) could also influence the future quantities of antimicrobials that will be used in animal production.…”
Section: Antimicrobials Use (Amu) In Food-producing Animalsmentioning
confidence: 99%
“…The province of Québec (Canada) adopted a new legislation in February 2019, to limit usage of category I AMs (e.g., third generation cephalosporins, fluoroquinolones or polymyxin B) of the Health Canada classification ( Government of Canada, 2009 ) in production animals ( Roy et al, 2020 ). This new regulation has been very effective in reducing the use of these AMs ( Millar et al, 2022 ). However, the effect of modification of antimicrobial use in food-producing animals on AMR gene dissemination in animal populations is not well described.…”
Section: Introductionmentioning
confidence: 99%
“…Our research team already established the portrait of both antimicrobial usage (AMU) and AMR in dairy farms in Québec prior to the regulation implementation ( Lardé et al, 2021 ; Massé et al, 2021 ), and the impact that the regulation had on AMU and AMR in E. coli isolates ( De Lagarde et al, 2022 ; Millar et al, 2022 ). We also characterized antimicrobial resistance genes in ESBL/AmpC isolates before the regulation implementation and determined the correlation between phenotypes and genotypes in these isolates ( Massé et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%